2001
DOI: 10.1002/dmrr.199
|View full text |Cite
|
Sign up to set email alerts
|

Coincident diabetes mellitus and primary hyperparathyroidism

Abstract: The prevalence of diabetes mellitus in primary hyperparathyroidism is approximately 8% and that of primary hyperparathyroidism in diabetic patients is approximately 1%. Both values are about three-fold higher than the respective expected prevalences in general populations. Patients with both disorders are over 40 years of age and 80% are female; 22% have type 1 and 78% type 2 diabetes. Primary hyperparathyroidism presents first in approximately 20% of patients, and diabetes mellitus in 40%; both disorders pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 28 publications
1
78
1
2
Order By: Relevance
“…This is supported by previous experimental data [8,9]. Increasing intracellular calcium levels have been shown to decrease the effect of insulin in adipocytes due to the reduced number of glucose transporters (GLUT4) and decreased insulin receptor activity [4,[28][29][30][31]. In an autopsy study performed in consecutive patients, it was shown that parathyroid adenomas and hyperplasia were far more common than the expected prevalence of overt hypercalcaemia [32].…”
Section: Possible Mechanisms For Observed Associationssupporting
confidence: 65%
See 1 more Smart Citation
“…This is supported by previous experimental data [8,9]. Increasing intracellular calcium levels have been shown to decrease the effect of insulin in adipocytes due to the reduced number of glucose transporters (GLUT4) and decreased insulin receptor activity [4,[28][29][30][31]. In an autopsy study performed in consecutive patients, it was shown that parathyroid adenomas and hyperplasia were far more common than the expected prevalence of overt hypercalcaemia [32].…”
Section: Possible Mechanisms For Observed Associationssupporting
confidence: 65%
“…Previous reports have also shown that patients with diabetes have elevated serum levels of calcium compared with nondiabetic individuals [3][4][5], and that the serum levels of calcium increase even further with decreasing metabolic control [3,4]. Moreover, in diseases with supranormal levels of serum calcium, such as primary hyperparathyroidism, there is a two-to fourfold higher prevalence of NIDDM and prediabetic states than in the general population [4,6,7]. Less is known about the relationship between serum calcium concentration and the two underlying causes of diabetes: insulin sensitivity and defective insulin secretion.…”
Section: Introductionmentioning
confidence: 97%
“…In diseases with markedly elevated serum calcium, such as primary hyperparathyroidism, there is a two-to four-fold higher prevalence of type 2 diabetes and glucose intolerance compared with the general population (5). Increased parathyroid hormone (PTH) could stimulate calcium channels to increase calcium influx and the levels of intracellular calcium, which would influence insulin sensitivity and hypertension (6).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with primary hyperparathyroidism (pHPT) the prevalence of type 2 diabetes (T2DM) is three times higher compared to healthy subjects (Taylor and Khaleeli, 2001). pHPT is also associated with impaired glucose tolerance (IGT) and reduced insulin sensitivity (IS) (Ljunghall et al, 1983).…”
Section: Introductionmentioning
confidence: 99%